Under lock and key: Incorporation of blockchain technology in the field of ophthalmic artificial intelligence for big data management - A perfect match? - Ramesh, Prasanna; Devadas, Aji; Ray, Prajnya; Ramesh, Shruthy; Joshua, Tensingh; Priyan, Vinoth; Ramesh, Meena; Rajasekaran, Ramesh; Ramesh, Prasanna Venkatesh; Devadas, Aji Kunnath; Ramesh, Shruthy Vaishali; Ramesh, Meena Kumari (Indian Journal of Ophthalmology, 2022)
Big data has been a game changer of machine learning. But, big data is a form of centralized version of data only available and accessible to the technology giants. A way to decentralize this data and make machine learning accessible to the smaller organizations is via the blockchain technology. This peer-to-peer network creates a common database accessible to those in the network. Furthermore, blockchain helps in securing the digital data and prevents data tampering due to human interactions. This technology keeps a constant track of the document in terms of creation, editing, etc., and makes this information accessible to all. It is a chain of data being distributed across many computers, with a database containing details about each transaction. This record helps in data security and prevents data modification. This technology also helps create big data from multiple sources of small data paving way for creating a well serving artificial intelligence model. Here in this manuscript, we discuss about the usage of blockchain, its current role in machine learning and challenges faced by it.